BOOK REVIEW OF KAZUO ISHIGURO’S NEVER LET ME GO - Hasanah, Uswatun (LANTERN (Journal on English Language, Culture and Literature), 2015)
Humansarethemostperfect creaturesof God. Humansare social creatureswho can not livealonein this world. Humanshave a needtointeractandcommunicatewith others. Without the helpof others, human beings can notwalkupright, and theyalsocan not developall the potentialtheyhave. Generally, humanslive in this worldtodo somethinguseful. Whentheycandosomethingforother people, theywillfeelhappyandproudof themselves. Sometimestohelp others, some people are willing tosacrifice their own lives. When someone issickand he or she needs blood donors, many people are willing todonatetheir bloodfor the sake ofhealingothers. Nownotonlybloodbutalsoorgans can bedonated. There are manyprosandconsregardingorgantransplantation, yet it is undeniable that organ transplantation can help the survival of others and help someone to extend his life. Although it is not allowed for commercial purposes, organ donation is legal for humanitarian purposes.